2020
DOI: 10.1007/s12325-020-01269-2
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Antibiotics in Clean-Contaminated Head and Neck Surgery: A Systematic Review and Meta-Analysis

Abstract: Background: The optimal evidence-based prophylactic antibiotic regimen for surgical site infections following major head and neck surgery remains a matter of debate. Methods: Medline, Cochrane, and Embase were searched for the current best evidence. Retrieved manuscripts were screened according to the PRISMA guidelines. Included studies dealt with patients over 18 years of age that underwent clean-contaminated head and neck surgery (P) and compared the effect of an intervention, perioperative administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 54 publications
(177 reference statements)
2
39
0
Order By: Relevance
“…Unlike many previous reports that included nonoral cavity sites, 1,5,7–10 highly variable antibiotic regimes, 6,7 or lacked explicit data on prophylactic antibiotics, 21 thereby introducing heterogeneity and/or bias, the current study examined a large sample of oral cavity resections that received a relatively standardized, uniform perioperative antibiotic regime. A broad spectrum of variables was examined for association with infective complications.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike many previous reports that included nonoral cavity sites, 1,5,7–10 highly variable antibiotic regimes, 6,7 or lacked explicit data on prophylactic antibiotics, 21 thereby introducing heterogeneity and/or bias, the current study examined a large sample of oral cavity resections that received a relatively standardized, uniform perioperative antibiotic regime. A broad spectrum of variables was examined for association with infective complications.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study showed a non-significant reduction in SSIs as a function of the administration of adequate antibiotic prophylaxis. There is some controversy between studies that show this relationship 25 , 26 and others that do not show the efficacy of antibiotic prophylaxis 27 , although a recent systematic review by Vander Porten et al 28 concludes that the administration of antibiotic prophylaxis clearly reduces the incidence of SSIs in clean-contaminated surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Infections associated with implantation of biomaterials are an unwanted complication of reconstructive surgery, often resulting in prolonged hospitalization, morphological and functional impairment [46]. Perioperative antibiotic prophylaxis leads to a decrease in the rate of infections associated with the implants but does not eradicate them [47][48][49][50]. Moreover, the implantation of biomaterials affects the host's innate local response and may increase the risk of infection [51].…”
Section: Discussionmentioning
confidence: 99%